2001
DOI: 10.1007/s001090100276
|View full text |Cite
|
Sign up to set email alerts
|

Flux of amino acids and energy substrates across the leg in weight-stable HIV-infected patients with acute opportunistic infections: indication of a slow protein wasting process

Abstract: Increased whole-body proteolysis with muscle protein net degradation has been suggested as one of the causes of weight loss in patients infected with human immunodeficiency virus (HIV). We studied the exchange rates of amino acids and energy substrates across the lower extremity in 16 HIV patients and 16 age-matched controls with similar body cell mass. The patients had either opportunistic infections or chronic diarrhea but no signs of clinical malnutrition. The following findings were obtained in the HIV pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Initial reports in which [ 13 C]leucine was used to assess changes in protein metabolism suggest that both protein synthesis and degradation increased (20). Later studies indicated that, in wasted patients, muscle protein synthesis might be downregulated, even when there is an overall increase in whole-body synthesis (21,22) and that the extent of change might be responsive to the level of activity or to nutritional or hormonal modulation (12,23,24). In addition to differences in body composition and nutritional intake, the contrasting results between studies may also reflect the marked clinical heterogeneity of patients with HIV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Initial reports in which [ 13 C]leucine was used to assess changes in protein metabolism suggest that both protein synthesis and degradation increased (20). Later studies indicated that, in wasted patients, muscle protein synthesis might be downregulated, even when there is an overall increase in whole-body synthesis (21,22) and that the extent of change might be responsive to the level of activity or to nutritional or hormonal modulation (12,23,24). In addition to differences in body composition and nutritional intake, the contrasting results between studies may also reflect the marked clinical heterogeneity of patients with HIV disease.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol, which is elevated in HIV-infected persons [1517], is a potent catabolic hormone, which increases rates of protein degradation and slows protein synthesis rates, especially in skeletal muscle [18]. Serum cortisol levels also appear to be the best predictor for insulin resistance followed by interleukin-6 (IL-6) in persons with inflammatory conditions [19].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, it has been documented that people infected with HIV experience changes at multiple levels of the hypothalamic-pituitary-adrenal axis, which can cause elevated cortisol levels ( 33 ). This alteration, being a potent catabolic pathway, could also increase protein degradation rates and slow down protein synthesis rates, especially in muscle mass; this is why it is implicated in muscle wasting associated with HIV infection ( 34 ).…”
Section: Discussionmentioning
confidence: 99%